2011
DOI: 10.1111/j.1601-6343.2011.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Tooth size and dental arch dimensions: a stereophotogrammetric study in Southeast Asian Malays

Abstract: This study has established new reference data for tooth size and arch dimensions in Malays and demonstrated patterns of variation that are relevant to anthropologists interested in making comparisons within and between different populations and also to clinicians developing treatment plans for their patients. The study confirmed the accuracy of the 3D photogrammetric method for measuring dental casts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 27 publications
5
37
0
2
Order By: Relevance
“…Arch dimension for maxillary and mandibular arches 18,19) Arch perimeter (Fig. 3 a1) The sum of fragmental lines from right and left side of the arch (these segments are starting from the distal contact of the Arch Length (Fig.…”
Section: Measurement Via Sm Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Arch dimension for maxillary and mandibular arches 18,19) Arch perimeter (Fig. 3 a1) The sum of fragmental lines from right and left side of the arch (these segments are starting from the distal contact of the Arch Length (Fig.…”
Section: Measurement Via Sm Techniquementioning
confidence: 99%
“…2a) The mesiodistal crown diameter of the tooth was measured from anatomical contact of one tooth to another on occlusal side perpendicular to the long axis of the teeth 1,4,11,19,20) . Buccolingual crown diameters (Fig.…”
Section: Measurement Via Sm Techniquementioning
confidence: 99%
“…These images were subjected to several comparisons between different expert professionals, which classified them into three basic shapes (quadrangular, triangular and oval), as suggested by several authors. [4][5][6]21 In relation to the sex, studies have affirmed that men have dental arch 16,22 and teeth larger than women. 16 Souza et al 6 (1997), evaluating a population of women between 20 and 25 years old, have observed the triangular shape of the upper central incisor as the most common (45.9%), followed by quadrangular (40.5) and oval (13.6).…”
Section: Jcdpmentioning
confidence: 99%
“…[4][5][6]21 In relation to the sex, studies have affirmed that men have dental arch 16,22 and teeth larger than women. 16 Souza et al 6 (1997), evaluating a population of women between 20 and 25 years old, have observed the triangular shape of the upper central incisor as the most common (45.9%), followed by quadrangular (40.5) and oval (13.6). Brunetto et al 23 (2011) registered that the oval shape was the most prevalent in both sexes.…”
Section: Jcdpmentioning
confidence: 99%
“…[2][3][4] Es sabido que existen asociaciones positivas entre las dimensiones del arco facial y dental, relaciones que se deben tomar en consideración cuando se hacen intentos para modificar el tamaño del arco dental como parte de un tratamiento de ortodoncia. 5 Existen muchas formas de realizar la medición de los anchos transversales. Uno de los métodos utilizados es tomando el centroide en el caso de caninos; 6 y las cúspides mesiovestibulares en el caso de molares.…”
unclassified